USE OF AERATED CONCRETE AS A BASIS FOR INCREASING THE ENERGY EFFICIENCY OF BUILDINGS: ANALYSIS OF THERMAL INSULATION PROPERTIES AND ENVIRONMENTAL EFFICIENCY - Климчук, Дмитро (SWorldJournal, 2024)
This paper investigates the thermal insulation and environmental properties of aerated concrete, an increasingly popular building material in modern construction due to its advantageous thermal performance and sustainability profile. Given the heightened